Quality of life in children with asthma as a marker of clinical stability - Cvejoska Cholakovska, Valentina; Vlashki, Emilija; Velikj Stefanovska, Vesna (Македонско лекарско друштво = Macedonian medical association, 2014)
Introduction. In order to improve asthma control, in the last decades an emphasis has been put on the assessment of quality of life (QL). The aim of the study was to assess the role of the Pediatric Asthma Quality of Life Questionnaire (PAQLQ) in order to assess the QL as a marker of clinical stability in asthmatic children. Methods. A total of 64 asthmatic children aged 7-17 years treated in an outpatient/hospital facility within the University Children’s Hospital in Skopje during 2 years were investigated. The children were assessed 3 times during a period of 3 months. To assess the asthma control the Clinical Stability Score (CSS) was used, and for the assessment of the QL the Macedonian version of the PAQLQ from Elizabeth Juniper was used, consisting of 23 questions organized into three domains: symptoms, activities, and emotions. The data were statistically analyzed using Statistic for Windows, version 7.0 and SPSS 14. Results. An increase in the average values of the PAQLQ scores was established, which means better control of asthma by the end of the 3-month follow-up. There was no statistically significant difference in the QL changes and the age of asthmatic children regarding all three domains and the overall score. Better PAQLQ scores were detected in children with better CSS. A significant improvement of all the PAQLQ scores in the case of beginning the inhaled corticosteroid therapy during the study was found. According to CSS, all of the children were classified as stable (good QL) at the end of the study compared to 78% stability at the beginning of the study. Conclusions. The Macedonian version of the PAQLQ can be used for assessment of the effects of anti-inflammatory therapy and for attainment of complete asthma control in children between 7 and 17 years of age.
Keywords: Asthma; children; quality of life